(untitled) (Al-Aasar, 2025)
This research paper presents a comparative and analytical study of the Qur’anic concept of Nafs (the self) and the foundational principles of modern psychological sciences. It explores the classifications, functions, and balance of the human Nafs as articulated in the Qur’an, interpreted through the perspectives of classical Islamic exegetes, scholars of Islamic psychology, and Sufi thinkers. The paper compares these Qur’anic insights with prominent Western psychological theories such as those of Freud, Jung, Maslow, and Cognitive Behavioral Therapy (CBT).It establishes that the Qur’anic notion of Nafs is not merely a psychological state but a moral, spiritual, and existential structure. The Qur’anic classification of Nafs—Nafs al-Ammarah (the commanding self), Nafs al-Lawwamah (the reproaching self), and Nafs al-Mutma’innah (the tranquil self)—mirrors stages of psychological and spiritual development.Furthermore, the Qur’anic model, which emphasizes purification (Tazkiyah), patience (Sabr), gratitude (Shukr), repentance (Tawbah), remembrance (Dhikr), and seeking forgiveness (Istighfar), is shown to be not only spiritually transformative but also in harmony with modern scientific findings regarding emotional and mental well-being.Contemporary research in neuroscience, positive psychology, and mindfulness confirms the profound effects of Qur’anic practices—such as remembrance, gratitude, patience, and self-accountability—on the brain, nervous system, and emotional regulation. The paper proposes the formulation of a Qur’an-based Islamic psychological model that views the human being holistically—integrating the soul (Ruh), intellect (‘Aql), heart (Qalb), and self (Nafs).This study emphasizes that Islamic psychological thought is not only a source of spiritual guidance but also a viable and effective framework within the context of modern scientific psychology. It argues that the lasting solution to contemporary mental and emotional crises lies not solely in clinical therapy, but in the divinely illuminated principles of the Qur’an.